1993
DOI: 10.1002/j.1460-2075.1993.tb05728.x
|View full text |Cite
|
Sign up to set email alerts
|

A signal sequence is not required for protein export in prlA mutants of Escherichia coli.

Abstract: The prlA/secY gene, which codes for an integral membrane protein component of the Escherichia coli protein export machinery, is the locus of the strongest suppressors of signal sequence mutations. We demonstrate that two exported proteins of E.coli, maltose‐binding protein and alkaline phosphatase, each lacking its entire signal sequence, are exported to the periplasm in several prlA mutants. The export efficiency can be substantial; in a strain carrying the prlA4 allele, 30% of signal‐sequenceless alkaline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
222
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(236 citation statements)
references
References 73 publications
9
222
0
5
Order By: Relevance
“…It recently was found that MBPA2-26 and an analogous signal peptide-less PhoA species can be exported to the periplasm, albeit somewhat inefficiently, in cells harboring prlA4 (12). Thus, the ability of prlA666 and other prl alleles to promote the export of MBPA2-26 was investigated, using growth on maltose minimal medium as a qualitative assay for MBP export.…”
Section: Resultsmentioning
confidence: 99%
“…It recently was found that MBPA2-26 and an analogous signal peptide-less PhoA species can be exported to the periplasm, albeit somewhat inefficiently, in cells harboring prlA4 (12). Thus, the ability of prlA666 and other prl alleles to promote the export of MBPA2-26 was investigated, using growth on maltose minimal medium as a qualitative assay for MBP export.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an effect on the topology of model membrane proteins is shown for two prlA alleles (31,32). Secretory proteins completely lacking the signal, but not cytosolic proteins, are still exported by prlA mutants in a SecB-dependent manner (33). This is accounted for by the fact that SecB recognizes secretory proteins within their mature sequences (34,35) and thus targets them to the translocon.…”
Section: Sec61p Mutations Affect Protein Orientation In Distinct Ways-mentioning
confidence: 99%
“…Therefore, in the case of the intermembrane shuttle, an import sequence-independent internalization of StAR into the mitochondrial intermembrane space is necessary and could be possible (Derman et al 1993). In the event where StAR functions outside mitochondria, StAR interactions with mitochondrial proteins are key for proper StAR function and still remain to be clearly identified.…”
Section: The Pros and Consmentioning
confidence: 99%